2006
DOI: 10.1111/j.1600-0447.2006.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Health resource utilization associated with switching to risperidone long‐acting injection

Abstract: Switching to RLAI was associated with a continuation of the trend for increased bed stay and use of healthcare resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 19 publications
(20 reference statements)
1
29
2
Order By: Relevance
“…These inconsistencies with our fi ndings at somewhat higher biweekly doses averaging 47 mg are unexplained, but may refl ect diff erences in case-selection. In fact, in the three Taylor et al trials [60,61,66] the study design allowed all prescribers to be informed that RLAI could be ordered for suitable patients with a DSM-IV diagnosis of schizophrenia or schizoaff ective disorder and known to be non-adherent to prescribed second-generation oral antipsychotics and intolerant of the adverse eff ects of conventional depot antipsichotics. In the study of 2004, Taylor et al [61] found that fi fty-one subjects (51 % ) discontinued RLAI within six months and the reason of discontinuation were: in 24 subjects (47 % ) the treatment was considered ineff ective (in 22 the treatment was considered ineffective by prescriber and there was an history of treatment resistance), in 18 (35 % ) patients refused to be treated and in 9 (18 % ) the treatment was not tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistencies with our fi ndings at somewhat higher biweekly doses averaging 47 mg are unexplained, but may refl ect diff erences in case-selection. In fact, in the three Taylor et al trials [60,61,66] the study design allowed all prescribers to be informed that RLAI could be ordered for suitable patients with a DSM-IV diagnosis of schizophrenia or schizoaff ective disorder and known to be non-adherent to prescribed second-generation oral antipsychotics and intolerant of the adverse eff ects of conventional depot antipsichotics. In the study of 2004, Taylor et al [61] found that fi fty-one subjects (51 % ) discontinued RLAI within six months and the reason of discontinuation were: in 24 subjects (47 % ) the treatment was considered ineff ective (in 22 the treatment was considered ineffective by prescriber and there was an history of treatment resistance), in 18 (35 % ) patients refused to be treated and in 9 (18 % ) the treatment was not tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…A mirror-image study performed with patients treated in public hospitals in Hong Kong 114 found that switching from oral to LAI therapy was associated with significantly lower total medical costs driven largely by lower hospitalization costs, although outpatient department and pharmacy costs significantly increased during the LAI treatment period. By contrast, a mirror-image study conducted in the United Kingdom, 115 which included predominantly patients with schizophrenia, reported that in the year following LAI therapy initiation, total health care costs significantly increased along with inpatient bed days, although the number of inpatient admissions declined. These unexpected results may be partially explained by the high level of illness severity reflected in the large proportion of study patients who started LAI therapy as inpatients.…”
Section: Effect Of Lais On Adherence and Costsmentioning
confidence: 93%
“…Observational studies of risperidone depot (Risperdal Consta) show that it is effective in some patient groups (Taylor et al , 2009b), but also that its effect on time spent in hospital can be beneficial (Niaz and Haddad, 2007; Taylor et al , 2008), neutral (Taylor et al , 2008), or adverse [in that some mirror-image studies show an increase in bed days after the initiation of risperidone depot (Young and Taylor, 2006; Taylor et al , 2009a)].…”
Section: Introductionmentioning
confidence: 99%